Transformasi UMKM Lampung Menuju Industri Halal: Peluang dan Tantangan di Era Bisnis Modern - Didik Kusno Aji Nugroho (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The transformation of Micro, Small, and Medium Enterprises (UMKM) in Lampung Province into the halal industry is a strategic step in responding to global market dynamics and the growing demands of Muslim consumers. With a Muslim-majority population, supportive government regulations, and abundant local raw material potential, Lampung holds great promise to become one of the leading centers for halal industry development in Indonesia. However, this transformation process still faces several serious challenges, such as limited understanding of halal standards, restricted access to certification, minimal technical assistance, and uneven education among UMKM actors. Through a SWOT analysis approach, this paper identifies the strengths, weaknesses, opportunities, and threats faced by UMKM in Lampung in the transformation process. The findings recommend collaborative strategies, digitalization, enhanced mentoring, and community-based partnerships to accelerate the development of an inclusive and sustainable halal industry ecosystem in the region. These findings are expected to serve as a policy reference and inspiration for other regions in developing Sharia-based economic potential.